MENTA50+ Online Game - Orosz, Anna Linda; Delgado-Peña, José Jesús (My University, 2014)
Serious Games are meant to assists learners in a playful, creative way to gain acquaintance with new skills or become better in things what we already know. They have much in common with educational games, at the same time they serve a broader scale of audience targeting learners regardless of age. Let’s build a Community Center. To create a Serious Game, first of all we needed an existing, real venue to provide an imaginary location to Menta Online. The United Kingdom has plenty of community centers where age is not an obstacle when it comes to learn new things or to warm up one’s social life. This gave us the idea to host our game in such community center: Our model Community House was inspired by Higham College in England, a used a leading centre of adult education. The online surface is the fruit of “Menta 50+ Learning to take actions for mental fitness and wellbeing in older age” Lifelong Learning Project financed by the European Commission.
Keywords: Educación de adultos; Online Platform; Mental fitness; Adult education; Educational resources; Online platform